Nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material as well as preparation method and application thereof
By preparing nitrogen, phosphorus, oxygen-doped soft/hard carbon nanofiber composites, the shortcomings of existing sodium ion battery anode materials in terms of sodium storage performance and rate performance are solved, and efficient sodium ion battery performance improvement is achieved, with low cost and process Simple.
Patent Information
- Application Number
- CN202411551491.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
The existing sodium ion battery negative electrode materials have shortcomings in sodium storage performance and rate performance. Traditional graphite materials have small layer spacing and are not suitable for sodium ion embedding and disengagement. Hard carbon materials have low carbon production, high production cost and poor conductivity. Soft carbon materials The graphitization conversion is easy to be transformed at high temperatures, limiting its sodium storage performance.
Using nitrogen, phosphorus and oxygen doped soft/hard carbon nanofiber composite materials as the negative electrode materials of sodium ion batteries, the use of petroleum coke and lignin as carbon sources, combined with electrospinning technology and high-temperature carbonization treatment, a high-temperature carbonization treatment was prepared to produce excellent sodium storage performance. Nanofiber composite material.
It improves the layer spacing and conductivity of carbon materials, reduces the internal ion diffusion resistance of the material, and improves the conductivity, porosity and surface area, thereby significantly improving the sodium storage performance and rate performance of sodium ion batteries, which is low in cost and simple in process.
Smart Images

Figure CN119419247A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy storage, and relates to a sodium ion battery negative electrode material and a preparation method and application thereof, and in particular to a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material and a preparation method and application thereof. Background Art
[0002] Energy storage and conversion technologies have been widely studied. Among the diverse energy storage technologies, sodium in sodium-ion batteries (SIBs) has attracted widespread attention not only because of its high natural abundance and low price, but also because of its similar chemical properties to lithium. As a key component of sodium-ion batteries, negative electrode materials have an important impact on the electrochemical performance and cost of batteries. Since the radius of sodium is larger than that of lithium, it often leads to a lower diffusion coefficient. Traditional graphite is not suitable for the insertion and extraction of sodium ions due to its small interlayer distance. Compared with graphite materials, hard carbon materials are considered to be suitable negative electrode materials for sodium-ion batteries due to their larger interlayer spacing. However, hard carbon materials have low carbon yield, high production cost and poor conductivity, which restricts large-scale commercialization. Soft carbon materials are more likely to undergo graphitization transformation at high temperatures, which will reduce the internal interlayer spacing of soft carbon, which is not conducive to sodium storage, but soft carbon materials have advantages in production cost, conductivity, rate performance, etc. Therefore, combining soft and hard carbon is a good strategy to obtain low-cost and high-performance SIBs negative electrode materials.
[0003] On the other hand, the efficient utilization of biomass materials has become a research hotspot in the pursuit of green energy and environmentally friendly materials. Lignin is a complex amorphous polyphenolic biopolymer, a key structural material for most plant support tissues, and an important component of biomass materials. It is the second largest biomass resource in the plant kingdom after cellulose and is an abundant renewable natural resource. The high carbon content and extensively bridged polymer structure of lignin can be used to produce high-value hard carbon materials. In addition, petroleum coke is a byproduct of the petroleum industry and a substance that can be obtained during coal production. It is rich in resources and has a high carbon yield, and can be used to make high-value activated carbon. The sufficient supply and economy of petroleum coke are considered to be conducive to the manufacture of soft carbon materials with higher added value. Petroleum coke is properly and conveniently converted and is expected to become a valuable resource for clean energy storage. According to current research, hard carbon and soft carbon each face different challenges as negative electrode materials for sodium ion batteries. Hard carbon exhibits a highly disordered structure, large interlayer spacing, and good porosity, but its curved atomic structure leads to low electronic and ionic conductivity, which affects rate performance and initial coulombic efficiency. At the same time, soft carbon has better conductivity and accelerates electron migration, but its more ordered structure and smaller interlayer spacing limit its capacity. Therefore, the present invention uses lignin as a hard carbon source and petroleum coke as a soft carbon source, combining the advantages of both, to prepare a soft and hard carbon composite material with excellent sodium storage performance. There are no related reports on the preparation method of nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite materials and their use as negative electrode materials in sodium ion batteries. Summary of the invention
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material comprises the following steps:
[0006] (1) Putting petroleum coke into a ball mill and ball milling at 500-800 r / min for 12-24 h; soaking the ball-milled petroleum coke in an acid solution with a concentration of 2-4 mol / L and stirring continuously for 12-24 h, then filtering, washing with distilled water until the filtrate is neutral, and finally drying in a forced air drying oven at 60-80° C. to obtain a petroleum coke precursor A;
[0007] (2) Adding petroleum coke precursor A, lignin, phosphoric acid, and polyacrylonitrile to N,N-dimethylformamide, heating and stirring to obtain a uniform spinning solution B; wherein the concentration of petroleum coke precursor A in N,N-dimethylformamide is 50-65 g / L; and the mass ratio of petroleum coke precursor A, lignin, phosphoric acid, and polyacrylonitrile is 1-1.3:1-1.5:0.7-1:1-1.4.
[0008] (3) The spinning solution B is subjected to electrostatic spinning technology under the conditions of an electrostatic voltage of 15 to 20 KV, a propulsion speed of the spinning solution of 6 to 10 μL / min, a receiving distance of 9 to 15 cm, a receiver rotation speed of 100 to 300 r / min, and an ambient temperature of 30 to 40°C to obtain lignin@petroleum coke composite nanofibers C.
[0009] (4) The lignin@petroleum coke composite nanofiber C is placed in a tubular furnace and pre-oxidized under the protection of an air atmosphere. The temperature is increased at a rate of 1 to 2°C / min, maintained at 250 to 300°C for 1 to 2 hours, and then naturally cooled to room temperature. The carbonization is then carried out under the protection of an inert atmosphere at a temperature increase rate of 2 to 3°C / min, maintained at 600 to 1300°C for 2 to 3 hours, and then naturally cooled to room temperature to obtain a nitrogen-phosphorus-oxygen doped soft / hard carbon nanofiber composite material.
[0010] Furthermore, the petroleum coke described in step 1 is any one of sponge coke or needle coke.
[0011] Furthermore, the concentration of the petroleum coke precursor A in N,N-dimethylformamide described in step 2 is 50-65 g / L; the mass ratio of the petroleum coke precursor A, lignin, phosphoric acid and polyacrylonitrile is 1-1.3:1-1.5:0.7-1:1-1.4.
[0012] Furthermore, the stirring environment described in step 2 is: humidity 10-40%, temperature 60-80°C.
[0013] Furthermore, the conditions of the electrospinning technology described in step 3 are: static voltage of 15-20 KV, propulsion speed of the spinning solution of 6-10 μL / min, receiving distance of 9-15 cm, receiver rotation speed of 100-300 r / min, and ambient temperature of 30-40°C.
[0014] Furthermore, the heating rate of the pre-oxidation process described in step 4 is 1-2°C / min, the target temperature is 250-300°C, the holding time is 1-2h, and the protective atmosphere is air.
[0015] Furthermore, the heating rate of the carbonization process described in step 4 is 2-3°C / min, the target temperature is 600-800°C, the holding time is 2-3h, and the protective atmosphere is nitrogen or argon.
[0016] The present invention also provides an application of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material as a negative electrode active material for a sodium ion battery. Specifically, the application of the composite material to a CR2032 button-type sodium ion battery comprises the following steps:
[0017] (a) mixing the negative electrode active material: Ketjen black: polyvinylidene fluoride in a mass ratio of 6 to 8:1 to 2:1, and stirring to obtain a solid mixture;
[0018] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 20:80 to 25:75, stirring evenly to obtain a slurry;
[0019] (c) coating the slurry obtained in step (b) on a copper foil, and preparing a sodium ion battery electrode sheet with a thickness of 13 to 22 μm after drying and rolling;
[0020] (d) The sodium ion battery electrode sheet obtained in step (c) is used as the electrode negative electrode sheet, Whatman glass fiber (GF / D) is used as the separator, and a mixed solvent of equal volumes of ethylene carbonate and propylene carbonate in 1 mol / L NaClO4 is used as the electrolyte to assemble a CR2032 button-type sodium ion battery in an argon-filled glove box.
[0021] Principle of the invention: The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of the present application is beneficial to improve the interlayer spacing and electrical conductivity of the carbon material through nitrogen, phosphorus and oxygen co-doping, and can provide more structural defects and improve the electrical conductivity of the material, thereby achieving the purpose of improving the sodium storage performance and rate performance of the material. The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of the present application has a mesh nanofiber structure, which significantly reduces the ion diffusion resistance inside the material, which will help to further improve the electrical conductivity, porosity and surface area, thereby making the electrolyte penetration rate faster. In addition, this unique one-dimensional nanostructure is more conducive to the transfer of electrons and ions, thereby producing faster electron transfer kinetics, which is beneficial to improving electrochemical performance.
[0022] The advantages and beneficial effects of the present invention are that the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared by the present invention can be used as an excellent negative electrode material for sodium ion batteries, has low cost and simple process, can give full play to the maximum value of petroleum coke and biomass carbon, and combines the advantages of soft carbon and hard carbon, providing ideas for the preparation of low-cost, high-performance carbon nanofiber materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope image of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of Example 1 of the present invention.
[0024] Figure 2 This is a transmission electron microscope image of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of Example 1 of the present invention.
[0025] Figure 3 This is the XRD of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to Example 1 of the present invention.
[0026] Figure 4 This is the Raman image of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of Example 1 of the present invention.
[0027] Figure 5 The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of Example 1 of the present invention is used as a negative electrode material for a sodium ion battery at 25 mAg -1 The charge and discharge curves below.
[0028] Figure 6 The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material of Example 1 of the present invention is used as a negative electrode material for a sodium ion battery at 25 mAg -1 The cycle performance diagram below. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to more fully understand the present invention, the preferred embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] 1. A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material, comprising the following steps:
[0032] (1) 5.0 g of petroleum coke was placed in a ball mill and ball milled at a speed of 800 r / min for 12 h. The ball-milled petroleum coke was then immersed in a 3 mol / L HCl solution, stirred for 12 h, filtered and washed with distilled water until the filtrate was neutral, and then dried in a forced air drying oven at 80° C. overnight to obtain a petroleum coke precursor A.
[0033] (2) 0.5 g of petroleum coke precursor A, 0.5 g of lignin, 0.35 g of H3PO4, and 0.5 g of polyacrylonitrile were added to 10 mL of N,N-dimethylformamide, and stirred continuously at a humidity of 25% and a temperature of 70°C to obtain a uniform spinning solution B.
[0034] (3) Spinning solution B is subjected to an electrostatic voltage of 15 KV, a propulsion speed of 7 μL / min, a receiving distance of 15 cm, a receiver rotation speed of 180 r / min, and an ambient temperature of 30°C to obtain lignin@petroleum coke composite nanofibers C.
[0035] (4) The lignin@petroleum coke composite nanofiber C is placed in a tubular furnace and first pre-oxidized in an air atmosphere by heating to 250°C at a heating rate of 1°C / min, maintaining for 1 hour, and then naturally cooling to room temperature; then carbonized in a nitrogen atmosphere by heating to 800°C at a heating rate of 2°C / min, maintaining for 2 hours, and then naturally cooling to room temperature to obtain a nitrogen-phosphorus-oxygen doped soft / hard carbon nanofiber composite material.
[0036] 2. Assembly and performance testing of CR2032 button-type sodium-ion batteries, including the following steps:
[0037] (a) mixing nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composites, polyvinylidene fluoride and Ketjen black in a mass ratio of 8:1:1 to obtain a solid mixture;
[0038] (b) mixing the solid mixture obtained in step (a) with N-methylpyrrolidone in a mass ratio of 25:75, stirring evenly, to obtain a slurry;
[0039] (c) coating the slurry obtained in step (b) on a copper foil, and preparing a sodium ion battery electrode sheet with a thickness of 10 to 24 μm after drying and rolling;
[0040] (d) The sodium ion battery electrode sheet obtained in step (c) is used as the negative electrode sheet, the sodium sheet is used as the positive electrode sheet, Whatman glass fiber (GF / D) is used as the diaphragm, and 1 mol / L NaClO4 is used as the electrolyte to assemble a CR2032 button-type sodium ion battery in a glove box filled with argon.
[0041] (e) The sodium ion battery assembled in step (d) is charged at 25 mA g in a voltage range of 0.01-3 V. -1 The first three cycles of charge and discharge activation were performed at a current density of 25 mA g -1 The charge and discharge cycle test was carried out with a current density of 1.
[0042] Example 2
[0043] 1. A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material, comprising the following steps:
[0044] (1) 5.0 g of petroleum coke was placed in a ball mill and ball milled at a speed of 700 r / min for 12 h. The ball milled petroleum coke was then immersed in a 4 mol / L HCl solution, stirred for 12 h, filtered and washed with distilled water until the filtrate was neutral, and then dried in a forced air drying oven at 80° C. overnight to obtain a petroleum coke precursor A.
[0045] (2) 0.6 g of petroleum coke precursor A, 0.6 g of lignin, 0.5 g of H3PO4, and 0.6 g of polyacrylonitrile were added to 10 mL of N,N-dimethylformamide, and stirred continuously at a humidity of 25% and a temperature of 80°C to obtain a uniform spinning solution B.
[0046] (3) The spinning solution B is subjected to electrostatic spinning technology at an electrostatic voltage of 18 KV, a propulsion speed of the spinning solution of 8 μL / min, a receiving distance of 15 cm, a receiver rotation speed of 200 r / min, and an ambient temperature of 35°C to obtain lignin@petroleum coke composite nanofibers C.
[0047] (4) The lignin@petroleum coke composite nanofiber C was placed in a tubular furnace and first pre-oxidized in an air atmosphere by heating to 280°C at a heating rate of 1.5°C / min, maintaining for 2 h, and then naturally cooling to room temperature; then carbonized in a nitrogen atmosphere by heating to 600°C at a heating rate of 2.5°C / min, maintaining for 2 h, and then naturally cooling to room temperature to obtain nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite materials.
[0048] 2. Assembly and performance test of CR2032 button-type sodium ion battery. This step is the same as that in Example 2.
[0049] Example 3
[0050] 1. A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material, comprising the following steps:
[0051] (1) 5.0 g of petroleum coke was placed in a ball mill and ball milled at a speed of 500 r / min for 24 h. The ball-milled petroleum coke was then immersed in a 2 mol / L HCl solution, stirred for 12 h, filtered and washed with distilled water until the filtrate was neutral, and then dried in a 60° C. forced air drying oven overnight to obtain a petroleum coke precursor A.
[0052] (2) 0.55 g of petroleum coke precursor A, 0.7 g of lignin, 0.3 g of H3PO4, and 0.5 g of polyacrylonitrile were added to 10 mL of N,N-dimethylformamide, and stirred continuously at a humidity of 20% and a temperature of 70°C to obtain a uniform spinning solution B.
[0053] (3) The spinning solution B is subjected to electrostatic voltage of 20 KV, a propulsion speed of 10 μL / min, a receiving distance of 10 cm, a receiver rotation speed of 250 r / min, and an ambient temperature of 40°C; and lignin@petroleum coke composite nanofibers C are obtained through electrospinning technology.
[0054] (4) The lignin@petroleum coke composite nanofiber C was placed in a tubular furnace and first pre-oxidized in an air atmosphere by heating to 250°C at a heating rate of 2°C / min, holding for 1 h, and then naturally cooling to room temperature; then carbonized in a nitrogen atmosphere by heating to 1000°C at a heating rate of 2°C / min, holding for 2 h, and then naturally cooling to room temperature to obtain nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite materials.
[0055] 2. Assembly and performance test of CR2032 button-type sodium ion battery. This step is the same as that in Example 2.
[0056] Example 4
[0057] 1. A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material, comprising the following steps:
[0058] (1) 5.0 g of petroleum coke was placed in a ball mill and ball milled at 600 r / min for 24 h. The ball milled petroleum coke was then immersed in a 3 mol / L HCl solution, stirred for 24 h, filtered and washed with distilled water until the filtrate was neutral, and then dried in a forced air drying oven at 80° C. overnight to obtain a petroleum coke precursor A.
[0059] (2) 0.65 g of petroleum coke precursor A, 0.75 g of lignin, 0.5 g of H3PO4, and 0.7 g of polyacrylonitrile were added to 10 mL of N,N-dimethylformamide, and stirred continuously at a humidity of 25% and a temperature of 70°C to obtain a uniform spinning solution B.
[0060] (3) The spinning solution B is subjected to electrostatic voltage of 16 KV, a propulsion speed of the spinning solution of 9 μL / min, a receiving distance of 12 cm, a receiver speed of 280 r / min, and an ambient temperature of 40° C. Through electrostatic spinning technology, lignin@petroleum coke composite nanofibers C are obtained.
[0061] (4) The lignin@petroleum coke composite nanofiber C was placed in a tubular furnace and first pre-oxidized in an air atmosphere by heating to 250°C at a heating rate of 1°C / min, holding for 1 h, and then naturally cooling to room temperature; then carbonized in a nitrogen atmosphere by heating to 1300°C at a heating rate of 2°C / min, holding for 2 h, and then naturally cooling to room temperature to obtain nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite materials.
[0062] 2. Assembly and performance test of CR2032 button-type sodium ion battery. This step is the same as that in Example 2.
[0063] Figure 1 This is the SEM of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1. It can be seen that the material presents a network cross-linked morphology.
[0064] Figure 2 This is the TEM image of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1, which is consistent with the SEM image.
[0065] Figure 3 This is the XRD of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1. The characteristic peaks near 24° and 44° correspond to the (002) and (100) crystal planes of amorphous carbon.
[0066] Figure 4 This is the Raman scan of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1, at 1340 and 1582 cm -1 There are two broad characteristic peaks at I, corresponding to the D band peak and the G band peak. D / I G The value is about 1.19, indicating that the material contains a large number of defects, a disordered structure, abundant pores and a large graphene interlayer spacing. These defects can provide more active sites for the reaction and shorten the Na + and the transmission path of electrons, improving material performance.
[0067] Figure 5 The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1 was used as the negative electrode material of sodium ion battery at 25 mAg -1 The charge and discharge curves of the 1st, 2nd, 3rd, 50th and 100th cycles at a current density of , and the charge and discharge curves from the 2nd to the 100th cycle are almost the same, which indicates that the prepared nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composites have good structural stability and good reversibility.
[0068] Figure 6 The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material prepared in Example 1 was used as the negative electrode material of sodium ion battery at 25 mAg -1 The cycle performance diagram shows that the discharge capacity is 316 mAh g after 100 cycles. -1 , superior to many current carbon negative electrode materials, and exhibits excellent cycle performance.
[0069] The sodium electrical performance results of Examples 1-4 are shown in Table 1.
[0070] Table 1 shows the sodium ion batteries of Examples 1 to 4 at 25 mAg -1 The capacity obtained from the 2nd and 100th cycles of charge and discharge tests under current.
[0071] Table 1
[0072]
[0073] As can be seen from Table 1, the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofibers of the present invention are used as electrode materials and applied to sodium ion batteries. -1 Under the condition of 100 cycles, the charging capacity is 280mAh g -1 The coulomb efficiency is above 97%, and the composite material has excellent sodium storage performance.
[0074] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material and its preparation method and application, characterized in that: The nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material is prepared from raw materials such as lignin, petroleum coke, polyacrylonitrile, phosphoric acid, etc.; wherein the diameter of the nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material is 140-230nm; the mass fraction of carbon is 65.47-78.86% by mass percentage, the mass fraction of nitrogen is 8.79-14.24%, the mass fraction of phosphorus is 3.24-6.11%, and the mass fraction of oxygen is 9.57-15.43%; the BET specific surface area is 37.26-57.49m 2 g -1 .
2. A method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material, characterized in that: The following steps are involved: (1) Putting petroleum coke into a ball mill and ball milling at 500-800 r / min for 12-24 h; soaking the ball-milled petroleum coke in an acid solution with a concentration of 2-4 mol / L and stirring continuously for 12-24 h, then filtering, washing with distilled water until the filtrate is neutral, and finally drying in a forced air drying oven at 60-80° C. to obtain a petroleum coke precursor A; (2) Adding petroleum coke precursor A, lignin, phosphoric acid, and polyacrylonitrile to N,N-dimethylformamide, heating and stirring to obtain a uniform spinning solution B; wherein the concentration of petroleum coke precursor A in N,N-dimethylformamide is 50-65 g / L; and the mass ratio of petroleum coke precursor A, lignin, phosphoric acid, and polyacrylonitrile is 1-1.3:1-1.5:0.7-1:1-1.
4. (3) The spinning solution B is subjected to electrostatic spinning technology under the conditions of an electrostatic voltage of 15 to 20 KV, a propulsion speed of the spinning solution of 6 to 10 μL / min, a receiving distance of 9 to 15 cm, a receiver rotation speed of 100 to 300 r / min, and an ambient temperature of 30 to 40°C to obtain lignin@petroleum coke composite nanofibers C. (4) The lignin@petroleum coke composite nanofiber C is placed in a tubular furnace and pre-oxidized under the protection of an air atmosphere. The temperature is increased at a rate of 1 to 2°C / min, maintained at 250 to 300°C for 1 to 2 hours, and then naturally cooled to room temperature. Then, the carbonization is carried out under the protection of an inert atmosphere at a rate of 2 to 3°C / min, maintained at 600 to 1300°C for 2 to 3 hours, and then naturally cooled to room temperature to obtain a nitrogen-phosphorus-oxygen doped soft / hard carbon nanofiber composite material.
3. The method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to claim 2, characterized in that: The petroleum coke described in step 1 is any one of sponge coke and needle coke.
4. The method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to claim 2, characterized in that: The acid in step 1 is any one of hydrochloric acid or hydrofluoric acid.
5. The method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to claim 2, characterized in that: The conditions of the electrospinning technology described in step 3 are: static voltage of 15-20KV, propulsion speed of the spinning solution of 6-10μL / min, receiving distance of 9-15cm, receiver rotation speed of 100-300r / min, and ambient temperature of 30-40℃.
6. The method for preparing a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to claim 2, characterized in that: The inert atmosphere in step 4 is nitrogen or argon or a nitrogen-argon mixed gas in any mixing ratio.
7. The use of a nitrogen, phosphorus and oxygen doped soft / hard carbon nanofiber composite material according to claim 1, characterized in that: Application as negative electrode material for sodium ion batteries.
Citation Information
Patent Citations
Carbon composite material for secondary battery, preparation method thereof and application thereof
CN109950548A
Nitrogen-doped porous carbon nanofiber composite material for lithium / sodium ion battery negative electrode and preparation method
CN111244412A
Hard carbon negative electrode material for lithium ion secondary battery and preparation method of hard carbon negative electrode material
CN113113601A
Modified phosphorus-doped polyacrylonitrile-based hard carbon negative electrode material and preparation process thereof
CN116960330A
One-dimensional porous silicon-carbon composite negative electrode material, preparation method, and application thereof
WO2022121137A1